2021
DOI: 10.1177/0956462420983992
|View full text |Cite
|
Sign up to set email alerts
|

Successful integration of HIV pre-exposure prophylaxis into a community-based HIV prevention program for female sex workers in Kolkata, India

Abstract: We assessed the impact of pre-exposure prophylaxis (PrEP) in the context of a community-based HIV program among female sex workers (FSWs) in Kolkata, India. This was an open-label, uncontrolled demonstration trial. HIV seronegative FSWs over 18 years were eligible. Participants were administered daily tenofovir/emtricitabine (TDF-FTC) with follow-up visits at months 1, 3, 6, 9, 12, and 15. Drug adherence was monitored by self-report, and a random subset of participants underwent plasma TDF testing. 843 women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 41 publications
1
11
1
1
Order By: Relevance
“…Reasons for PrEP discontinuation included moving out of town, 7 25 returning to the country of origin, 27 pregnancy, 25 27 no longer doing sex work, 7 24 not taking a daily pill, 7 24 breast feeding, HIV seroconversion, desire to marry, partner’s request, 27 serious injury or death, 25 and being in police custody. 24 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reasons for PrEP discontinuation included moving out of town, 7 25 returning to the country of origin, 27 pregnancy, 25 27 no longer doing sex work, 7 24 not taking a daily pill, 7 24 breast feeding, HIV seroconversion, desire to marry, partner’s request, 27 serious injury or death, 25 and being in police custody. 24 …”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported PrEP adherence 24 25 27 28 32 ( online supplemental table 3 ), of which four studies reported facility models. 24 25 27 28 The most common adherence measure was self-report.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were analyzed from prospective studies involving oral F/TDF for PrEP in cisgender women and adolescents conducted between 2012, the year F/TDF for PrEP was approved for use in the US, and 2020. These studies were performed as part of the postmarketing commitment to the FDA and were either demonstration projects (n = 7) or open-label studies (n = 4), with 7 conducted in sub-Saharan Africa, 2 in India, and 2 in the US (Table). Study populations varied, but all included individuals who could benefit from PrEP and persons in serodiscordant (1 partner living with HIV and 1 partner without HIV) relationships, adolescent females and young women, and female sex workers.…”
Section: Methodsmentioning
confidence: 99%